THE PRACTICE OF HALAL CONCEPT AMONG FOOD PREMISES IN PERLIS: THE HYGIENE PERSPECTIVE - Abdul Lateb, Nadiah; Md Yusof, Syarifah (International Journal of Supply Chain Management, 2020)
The term halal is well known in Malaysia, especially in Muslim society. However, the practice of halal concept among Muslim food operators is questionable and doubtful. The cleanliness aspect of hygiene is one of the main aspects that contributed to the concept of halal in Islam, besides the aspect of pure, safety and quality. There are many issues and cases reported in the media regarding the cleanliness of the food premises in Malaysia. Many cases of food poisoning originated from poor food preparation and improper cleaning by the food premise operators themselves. These practices could lead to serious contamination and food poisoning to customers. Thus, this study is conducted to examine the practice of halal concept in the aspect of hygiene among food premises. The study is qualitative based research by adopting a phenomenology approach. Data was collected through an in-depth interview with six food premise operators in Perlis. Data are analyzed using the inductive analysis approach by using Creswell analysis. Results showed that only one of the informants did not apply the hygiene practice very well. Overall, all of the informants have good understanding and awareness in practicing the halal concept at their food premises. Thus, high awareness and commitment about the practice of hygiene in the halal concept are needed especially to food premise operators. The municipal authority and health department should enhance their monitoring enforcement towards the operations of food premises to make sure all food premises apply good hygiene practices in their daily operation.